Welfare migration in Europe and the cost of a harmonised social assistance - Giacomo De Giorgi; Michele Pellizzari (Institute for the Study of Labor (IZA), 2006)
The enlargement of the European Union has increased concerns about the role of generous welfare transfers in attracting migrants. This paper explores the issue of welfare migration across the 15 countries of the pre-enlargement Union and finds a significant but small effect of the generosity of welfare on migration decisions. This effect, however, is still large enough to distort the distribution of migration flows and, possibly, offset the potential benefits of migration as an inflow of mobile labour into countries with traditionally sedentary native workers. A possible way to eliminate these distortions is the harmonisation of welfare at the level of the Union. The second part of the paper estimates the costs and benefits of what could be a first step in this direction: the introduction of a uniform European minimum income. The results show that, for a realistic minimum income threshold, the new system would cost about three quarters of what is currently spent on housing and social assistance benefits. Despite its reasonable cost, the distribution of net donors and net receivers across countries is such that the actual implementation of this system would be politically problematic.
Keywords: J61; 330; EU enlargement; migration; welfare state